Branched-chain amino acid, meat intake and risk of type 2 diabetes in the Women's Health Initiative. Issue 11 (19th July 2017) - Isanejad, Masoud; LaCroix, Andrea Z.; Thomson, Cynthia A.; Tinker, Lesley; Larson, Joseph C.; Qi, Qibin; Qi, Lihong; Cooper-DeHoff, Rhonda M.; Phillips, Lawrence S.; Prentice, Ross L.; Beasley, Jeannette M.
Abstract: Knowledge regarding association of dietary branched-chain amino acid (BCAA) and type 2 diabetes (T2D), and the contribution of BCAA from meat to the risk of T2D are scarce. We evaluated associations between dietary BCAA intake, meat intake, interaction between BCAA and meat intake and risk of T2D. Data analyses were performed for 74 155 participants aged 50−79 years at baseline from the Women's Health Initiative for up to 15 years of follow-up. We excluded from analysis participants with treated T2D, and factors potentially associated with T2D or missing covariate data. The BCAA and total meat intake was estimated from FFQ. Using Cox proportional hazards models, we assessed the relationship between BCAA intake, meat intake, and T2D, adjusting for confounders. A 20 % increment in total BCAA intake (g/d and %energy) was associated with a 7 % higher risk for T2D (hazard ratio (HR) 1·07; 95 % CI 1·05, 1·09). For total meat intake, a 20 % increment was associated with a 4 % higher risk of T2D (HR 1·04; 95 % CI 1·03, 1·05). The associations between BCAA intake and T2D were attenuated but remained significant after adjustment for total meat intake. These relations did not materially differ with or without adjustment for BMI. Our results suggest that dietary BCAA and meat intake are positively associated with T2D among postmenopausal women. The association of BCAA and diabetes risk was attenuated but remained positive after adjustment for meat intake suggesting that BCAA intake in part but not in full is contributing to the association of meat with T2D risk.